SYNERGISTIC IMMUNOMODULATORY ACTIVITY OF AQUEOUS ROOT EXTRACT OF ASPARAGUS RACEMOSUS WILLD AND ETHANOL WHOLE PLANT EXTRACT OF BOERHAVIA DIFFUSA LINN - KUMARI, AMRITA; CHAKRABORTY, MAINAK; SARKAR, NILANJAN; BOSE, SEKHAR KUMAR; ROY, KALYAN; KARUNAKARAN, GAUTHAMAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: On the basis of traditional use and Ethno pharmacological evidences Boerhavia diffusa whole plant and root part of Asparagus racemosus (Shatavari) both are widely used to enhance the immunity. But in combination there is no scientific evidence so current study was designed. Methods: Laboratory based study, namely, carbon clearance, cyclophosphamide induced immune suppression and neutrophil adhesion was designed using mice as an experimental animals in different combination of aqueous whole plant extract of B. diffusa and methanol extract of root part of A. racemosus were used as a test drug in the ratio 1:1, 1:2, and 2:1 (100 mg/kg) against the established standard drug Ashwagandha. Results: The results revealed that animals treated with combined extract (1:1, 1:2, and 2:1) at a dose of 100 mg/kg increase rate of carbon clearance from blood, there is significance alternation in blood parameter in cyclophosphamide group and also improve the Neutrophil adhesion when treated with different combination of polyherbal formulation treated groups. Conclusion: The polyherbal formulation in different ratio showing good significant immunomodulatory activity as compare to standard.